Analisis Daya Dukung dan Penurunan Pondasi Dangkal dan Pondasi Dalam Diatas Tanah Lunak - Shobibur Rohman Zen; Muhammad Edy Saputro; Rifqi Brilyant Arief (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Soft soil in the Kaligawe Road area of Semarang is characterized by low bearing capacity and high compressibility, posing significant challenges in foundation planning for buildings. This study analyzes the bearing capacity and primary consolidation settlement of shallow foundations (spread footing) and deep foundations (pile foundation) on soft soil using SPT data from borehole BH-06 up to 60 m depth. Bearing capacity calculations were performed using the Meyerhof (1956) method for shallow foundations and the Meyerhof (1976) method for deep foundations, while primary consolidation settlement was calculated based on Terzaghi's consolidation theory with parameters Cc = 0.334 and e₀ = 1.347–1.410. The results indicate that the bearing capacity of deep foundations increases consistently with depth and pile diameter, with skin friction dominating the total bearing capacity. A settlement comparison at equivalent allowable bearing capacity values shows that shallow foundations produce the largest settlement (average Sc = 0.093 m), followed by deep foundations in a 2×2 configuration (average Sc = 0.063 m), while deep foundations in a 2×1 configuration yield the smallest settlement (average Sc = 0.037 m). Therefore, the 2×1 pile configuration is recommended as the most optimal foundation system for soft soil conditions at the study location.